2023
DOI: 10.1039/d2fo03734c
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the foaming properties of brewer's spent grain protein by ultrasound treatment and glycation reaction

Abstract: The denaturation state and relatively poor solubility of brewer’s spent grain protein (BSGP) have limited its industrial application. Ultrasound treatment and glycation reaction were applied to improve structural and foaming...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Chen et al (2022) coupled dextrin with rice protein (RP) using ultrasound-assisted glycosylation, and the results showed that the modified protein had a solubility as high as 90.6% under ultrasound conditions of 600 W, 82 °C for 22 min. Li et al (2023) glycosylated modified beer spent grain protein (BSGP) and found that the solubility of the modified protein increased, possibly due to the increased hydrophilicity and hydrogen bonding capacity, altering the distribution of molecular charges and increasing the repulsive forces between protein molecules, thereby enhancing the affinity between the protein and the solvent.…”
Section: Solubilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al (2022) coupled dextrin with rice protein (RP) using ultrasound-assisted glycosylation, and the results showed that the modified protein had a solubility as high as 90.6% under ultrasound conditions of 600 W, 82 °C for 22 min. Li et al (2023) glycosylated modified beer spent grain protein (BSGP) and found that the solubility of the modified protein increased, possibly due to the increased hydrophilicity and hydrogen bonding capacity, altering the distribution of molecular charges and increasing the repulsive forces between protein molecules, thereby enhancing the affinity between the protein and the solvent.…”
Section: Solubilitymentioning
confidence: 99%
“…Li et al . (2023) glycosylated modified beer spent grain protein (BSGP) and found that the solubility of the modified protein increased, possibly due to the increased hydrophilicity and hydrogen bonding capacity, altering the distribution of molecular charges and increasing the repulsive forces between protein molecules, thereby enhancing the affinity between the protein and the solvent.…”
Section: Improvement Of Protein Functional Properties By Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Solubility is one of the most important functional properties of proteins, because in many food applications, proteins should possess good solubility. The solubility is dependent on ion hydration and the electrostatic repulsion between the molecules [49]. As the aggregation and degradation of proteins are associated with their solubility, the lowest solubility is measured under acidic conditions, around the isoelectric pH of the protein.…”
Section: Solubilitymentioning
confidence: 99%
“…In other studies, the antagonistic effect on the solubility of the conjugates when using alternative technologies has been reported. Li et al [49] investigated the effect of US (500 W, 40 min), conventional wet heating (60 • C, 90 min), and US-assisted glycation (500 W, 60 • C, 40 min) on the solubility of the brewer's spent grain protein-maltose conjugates. The conjugates prepared by US-assisted glycation had lower solubility (75%) than the wet-heating treatment (80%).…”
Section: Solubilitymentioning
confidence: 99%